Intravenous Ketamine Bolus(es) for the Treatment of Status Epilepticus, Refractory Status Epilepticus, and Cluster Seizures: A Retrospective Study of 15 Dogs - Roynard, Patrick; Bilderback, Ann; Dewey, Curtis Wells (Frontiers in Veterinary Science, 2021)
Status epilepticus (SE) and cluster seizures (CS) are common occurrences in veterinary neurology and frequent reasons of admission to veterinary hospitals. With prolonged seizure activity, gamma amino-butyric acid (GABA) receptors (GABAa receptors) become inactive, leading to a state of pharmacoresistance to benzodiazepines and other GABAergic medications, which is called refractory status epilepticus (RSE). Prolonged seizure activity is also associated with overexpression of N-methyl-D-aspartic (NMDA) receptors. Rodent models have shown the efficacy of ketamine (KET) in treating RSE, and its use has been reported in one canine case of RSE. Boluses of KET 5 mg/kg IV have become the preferred treatment for RSE in our hospital. A retrospective study was performed to evaluate and report our experience with KET IV bolus to treat prolonged and/or repeated seizure activity in cases of canine CS, SE, and RSE. A total of 15 dogs were retrieved, for 20 hospitalizations and 28 KET IV injections over 3 years. KET IV boluses were used 12 times for RSE (9 generalized seizures, 3 focal seizures) and KET terminated the episode of RSE 12/12 times (100%); however, seizures recurred 4/12 times (33%) within ≤6 h of KET IV bolus. When used for CS apart from episodes of RSE, KET IV bolus was associated with termination of the CS episode only 4/14 times (29%). Only 4/28 (14%) KET IV boluses were associated with adverse effects imputable only to the use of KET. One dog experienced a short, self-limited seizure activity during administration of KET IV, which was most likely related to a pre-mature use of KET IV (i.e., before GABAergic resistance and NMDA receptor overexpression had taken place). This study indicates that KET 5 mg/kg IV bolus may be successful for the treatment of RSE in dogs.